A Study on the Tensile Strength of Ice as a Function of Grain Size - Currier,J H; Schulson,E M; St Lawrence,W F (1983)
An analysis of ice fracture that incorporates dislocation mechanics and linear elastic fracture mechanics is discussed. The derived relationships predict a brittle to ductile transition in polycrystalline ice under tension with a Hall-Petch type dependence of brittle fracture strength on grain size. A uniaxial tensile testing technique, including specimen preparation and loading system design was developed and employed to verify the model. The tensile strength of ice in purely brittle fracture was found to vary with the square root of the reciprocal of grain size, supporting the relationship that the theory suggests. The inherent strength of the ice lattice and the Hall-Petch slope are evaluated and findings discussed in relation to previous results. Monitoring of acoustic emissions was incorporated in the tests, providing insights into the process of microfracture during ice deformation.